ATENDIMENTO PSICOLÓGICO A MULHERES EM SITUAÇÃO DE VIOLÊNCIA DOMÉSTICA - Campos, Iris F. A.; Meira, Giane; Vogt, Margit; Marin, Mariana B.; Frantz, Marilia Z.; Aimi, Martina S. (Salão do Conhecimento, 2013)
Resumo